Atorvastatin Increases miR‐124a Expression: A Mechanism of Gamt Modulation in Liver Cells. Issue 11 (9th September 2015) - Phulukdaree, Alisa; Moodley, Devapregasan; Khan, Sajidah; Chuturgoon, Anil A.
ABSTRACT: Atorvastatin is used to control cholesterol and lipid levels in hyperlipidaemic and hypercholesterolaemic patients. Myopathy and hepatotoxicity, however, have been reported as side effects in a small percentage of statin users. This study aimed to investigate the cytotoxicity and the effect of atorvastatin on microRNA expression in HepG2 cells. The methylthiazol tetrazolium assay was used to assess hepatocyte viability and at 20 μM atorvastatin (24 h) treatment were 82 ± 1.5% viable ( P = 0.0002). Levels of intracellular ATP in cells treated with 20 μM atorvastatin were reduced by 1.25‐fold, P = 0.002. Cytotoxicity, measured by the release of intracellular lactate dehydrogenase, was increased from 0.95 ± 0.29 units in control cells to 1.12 ± 0.02 units ( P = 0.002) in atorvastatin treated cells. A panel of 84‐miRNA species was used to evaluate the effect of atorvastatin on miRNA expression. MiR‐124a was significantly up‐regulated by atorvastatin (12.94‐fold). A significant decrease in GAMT expression (3.54‐fold) was observed in atorvastatin treated cells following quantitative PCR analysis. In addition, western blotting data showed GAMT protein levels were significantly lower than the controls (3.02‐fold) and analysis of creatine levels in treated cells showed a significant decrease in the atorvastatin treated culture supernatant compared to control culture supernatant (32.33 ± 3.51 μM/l vs. 59.67 ± 1.52μM/l, P = 0.0056). This is the first study to show that atorvastatin up‐regulates miR‐124a levels and consequently modulates GAMT expression in hepatocytes. J. Cell. Biochem. 116: 2620–2627, 2015. © 2015 Wiley Periodicals, Inc.